Key Cytokines of Adaptive Immunity Are Differentially Induced in Rainbow Trout Kidney by a Group of Structurally Related Geranyl Aromatic Derivatives - Imarai-Bahamonde, C; Modak-Canobra, B; Maisey-Munoz, K; Valenzuela-Montenegro, B; Soto-Aguilera, S (Academic Press, 2016)
Filifolinone is a semi-synthetic terpenoid derivative obtained from Heliotropium filifolium that increases the expression level of pro-inflammatory and anti-inflammatory cytokines in kidney cells of salmon. Because cytokines are produced in response to a foreign organism and by distinct other signals modulating immune responses, we further studied the potential immunomodulatory effects of a group of structural related terpenoid derivatives from H. filifolium on salmonids to determine the relationship between the chemical structure of the derivatives and their ability to modify cytokine expression and the lymphoid content. The resin and four 3H-spiro 1-benzofuran-2,1 -cyclohexane derivatives were tested in vivo in rainbow trout (Oncorhynchus mykiss) by quantifying the transcript levels of antiviral and T helper-type cytokines and T and B cells in the kidney. Three of the four terpenoids differ only in the C-7 substituent of the cyclohexane and the presence of the ketone group at this position in Filifolinone appeared responsible of an important up-regulation of IFN-α1, IFN-γ, IL-4/13A and IL-17D in the kidney of the treated trout. In addition, the absence of a methoxy group in carbon 7 of the benzene ring, found in all compounds but not in Folifolinoic acid, produced a significant reduction of IFN-γ, IL-12 and IL-4/13A transcripts. B cells were not affected by the compound treatment but Filifolinoic acid and the resin induced a significant reduction of T cells. Altogether, results showed that immunomodulating responses observed in the trout by effect of 3H-spiro 1-benzofuran-2,1 -cyclohexane derivatives is related to the presence of the ketone group in the carbon 7 and the methoxy group in carbon 7 of the benzene ring, being Filifolinone the most active immunostimulatory compound identified. © 2015 Elsevier Ltd.